How the Depletion in Mineral Major Elements Affects Grapevine (Vitis vinifera L.) Primary Cell Wall - Goulao, Luís F.; Fernandes, João C.; Amâncio, Sara (Frontiers in Plant Science, 2017)
The noteworthy fine remodeling that plant cell walls (CWs) undergo to adapt to developmental, physiological and environmental cues and the observation that its composition and dynamics differ between species represents an opportunity to couple crop species agronomic studies with research on CW modifications. Vitis vinifera is one of the most important crops from an economic point-of-view due to the high value of the fruit, predominantly for winemaking. The availability of some information related to this species’ CWs allows researching its responses to imposed conditions that affect the plant’s development. Mineral deficiency, in particular nitrogen, phosphorus, potassium and sulfur, strongly affects plant metabolism, reducing both growth and crop yield. Despite the importance of mineral nutrition in development, its influence on CW synthesis and modifications is still insufficiently documented. Addressing this knowledge gap, V. vinifera experimental models were used to study CW responses to imposed mineral depletion in unorganized (callus) and organized (shoots) tissues. The discussion of the obtained results is the main focus of this review. Callus and shoots submitted to mineral restriction are impaired in specific CW components, predominantly cellulose. Reorganization on structure and deposition of several other polymers, in particular the degree and pattern of pectin methyl-esterification and the amount of xyloglucan (XyG), arabinan and extensin, is also observed. In view of recently proposed CW models that consider biomechanical hotspots and direct linkages between pectins and XyG/cellulose, the outcome of these modifications in explaining maintenance of CW integrity through compensatory stiffening can be debated. Nutrient stresses do not affect evenly all tissues with undifferentiated callus tissues showing more pronounced responses, followed by shoot mature internodes, and then newly formed internodes. The impact of nitrogen depletion leads to more noticeable responses, supporting this nutrient’s primary role in plant development and metabolism. The consequential compensatory mechanisms highlight the pivotal role of CW in rearranging under environmental stresses.